Cassane-type Diterpenes from the Seeds of Caesalpinia minax with Their Antineoplastic Activity - Ma, Guo-Xu; Xu, Xu-Dong; Cao, Li; Yuan, Jing-Quan; Yang, Jun-Shan; Ma, Li-Yan (Planta Medica, 2012)
Five new cassane-type diterpenes, neocaesalpin AA (1), neocaesalpin AB (2), neocaesalpin AC (3), neocaesalpin AD (4) and neocaesalpin AE (5), were isolated from Caesalpinia minax together with three known compounds, 12α-methoxyl,5α,14β-dihydroxy-1α,6α,7β-triacetoxycass-13(15)-en-16,12-olide (6), spirocaesalmin (7) and magnicaesalpin (8). Their structures were elucidated based on 1D and 2D NMR, MS and CD analyses. Compounds 1–6 were tested against Hela, HCT-8, HepG-2, MCF-7 and A549 cancer cells and showed moderate cytotoxicity with IC50 values from 18.4 to 83.9 µM.
Keywords: Fabaceae; Caesalpinia minax; cassane-type diterpene; cytotoxicity